2005
DOI: 10.1021/jp0529117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isomer Geometry on the Steady-State Absorption Spectra and Femtosecond Time-Resolved Dynamics of Carotenoids

Abstract: Steady-state absorption and femtosecond time-resolved optical spectroscopic studies have been carried out on all-trans-beta-carotene, 15,15'-cis-beta-carotene, all-trans-spheroidene, and 13,14-locked-cis-spheroidene. We examine in detail the effect of isomer geometry on the spectroscopic properties and photophysics of the low-lying S(1) (2(1)A(g)(-)) and S(2) (1(1)B(u)(+)) excited states of these molecules. The experiments on 13,14-locked-cis-spheroidene, a molecule incapable of undergoing cis-to-trans isomeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 68 publications
6
47
1
Order By: Relevance
“…The profiles were normalized at their maxima; f the steady-state absorption spectrum (dotted line) and the TA spectrum taken in NIR range expressed in wavenumber scale and overlaid to obtain the best peak-valley agreement. The shift required to bring the spectra to coincidence defines the S 1 (2 1 A g -) state energy (11,350 cm -1 ) Photosynth Res (2011) 110:49-60 53 spectral shape and lifetime of *0.5 ps suggest that this EADS is associated with the ESA occurring from the vibrationally not equilibrated S 1 (2 1 A g -) state that was observed for a number of Cars with N = 11 and shorter in solvent environment as well as in a protein (Billsten et al 2003(Billsten et al , 2005Larsen et al 2003;Niedzwiedzki et al 2007Niedzwiedzki et al , 2009Papagiannakis et al 2006;Pendon et al 2005;Wohlleben et al 2003Wohlleben et al , 2004. The lifetime of the S 1 (2 1 A g -) state obtained from the fitting is 3.4 ps.…”
Section: Resultsmentioning
confidence: 89%
“…The profiles were normalized at their maxima; f the steady-state absorption spectrum (dotted line) and the TA spectrum taken in NIR range expressed in wavenumber scale and overlaid to obtain the best peak-valley agreement. The shift required to bring the spectra to coincidence defines the S 1 (2 1 A g -) state energy (11,350 cm -1 ) Photosynth Res (2011) 110:49-60 53 spectral shape and lifetime of *0.5 ps suggest that this EADS is associated with the ESA occurring from the vibrationally not equilibrated S 1 (2 1 A g -) state that was observed for a number of Cars with N = 11 and shorter in solvent environment as well as in a protein (Billsten et al 2003(Billsten et al , 2005Larsen et al 2003;Niedzwiedzki et al 2007Niedzwiedzki et al , 2009Papagiannakis et al 2006;Pendon et al 2005;Wohlleben et al 2003Wohlleben et al , 2004. The lifetime of the S 1 (2 1 A g -) state obtained from the fitting is 3.4 ps.…”
Section: Resultsmentioning
confidence: 89%
“…Such a transition is expected to be broader and red-shifted compared to transitions originating from a vibrationally relaxed S 1 (2 1 A g -) state. 11,[35][36][37] Of the models tested here, target model 2 ( Figure 5D) works best to account for the data from lutein and zeaxanthin. The global fits are shown in Figure 8 and the S 1 (2 1 A g -) and S* state lifetimes obtained from this model are summarized in Figure 9.…”
Section: Discussionmentioning
confidence: 99%
“…The vibrationally hot S 1 (2 1 A g -) relaxes within several hundreds of femtoseconds. 31, [35][36][37] For most xanthophylls, S* and S 1 (2 1 A g -) decay to the ground state in the range of 1-40 ps. 11 In the present work, ultrafast time-resolved spectroscopy was carried out at 77 K to examine the spectroscopic properties and dynamics of three major xanthophylls from green plants, violaxanthin, lutein, and zeaxanthin ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…32,[35][36][37] Basically, they studied the reconstituted carotenoidless Rb. sphaeroides R-26.1 in which a locked-cis-SPO, which is supposed not to isomerize to all-trans configuration, was incorporated and showed that no difference in either spectroscopic properties or the photochemistry compared to the wild-type Rb.…”
Section: Does Locked-1314-cis-spheroidene Has a Crossing Potential Cmentioning
confidence: 99%
“…Yet, studies by Pendon et al [35][36][37] in 2006 concluded against the hypothesis drawn by Koyama and co-workers. They reported ultrafast time-resolved spectroscopic studies of two pairs of stable geometric isomers of carotenoids including trans-SPO and 13,14-locked-cis-SPO, the latter of which is incapable of undergoing cis-to-trans isomerization at C13-C14…”
mentioning
confidence: 94%